Respuestas

2012-05-11T16:58:45+02:00

buenos dias.a+bal cubo=(a+b)al cubo=aalcuadrado+3aalcuadradob+3abalcuadrado+balcuadrado
a-balcubo=(a-b)alcubo=aalcuadrado-3aalcuadradob+3abalcuadrado-balcuadrado
(a+1)alcubo=aalcubo+3aalcuadrado(1)+3a(1)alcuadrado+1alcubo=aalcubo+3aalcuadrado+3a+1....(x-2)alcubo=xalcubo-3xalcuadrado(2)+3x82alcuadrado)-2alcubo=xalcubo-6xalcuadrado+12x-8....(4x+5)alcubo=(4x)alcubo+3(4x)alcuadrado(5)+3(4x)(5)alcuadrado+5alcubo=64xalcubo+240xalcuadrado+300x+125
(xalcuadrado-3y)alcubo=(xalcuadrado)alcubo-3(xalcxuadrado)alcuadrado(3y)+3xalcuadrado(3y)alcuadrado-(3y)alcubo=xala6ta-9xala4tay+27xalcuadradoyalcuadrado-27yalcubo.saludos.